Fiscal and Macroeconomic Impact of Privatization - Davis, Jeffrey (Occasional Papers; Occasional Paper, 2000)
Privatization has been a key element of structural reform in many developing and transition economies during the last decade. This paper examines the fiscal and macroeconomic issues involved in the privatization of nonfinancial public enterprises in these economies. It considers issues such as the factors determining the proceeds from privatization and the amount accruing to the budget, the uses of proceeds, the impact of privatization on the budget and macroeconomic aggregates, and the privatization component of IMF-supported programs. The empirical evidence draws on case study countries that reflect geographical diversity and are representative of a range of privatization experience in developing and transition economies.